(untitled) (American Journal of Medical Science and Innovation, 2024)
This paper discusses the complex relationship between obesity and male infertility in a detailed manner. According to the introduction, obesity-related infertility is importantly discussed since it affects some 15% of couples in which half cases are attributed for obesity-related infertility is important to discuss since it affects some 15% of couples, and half of cases are attributed to male factors. The body of the analysis discusses various factors related to obesity-associated male reproduction implications, including endocrinopathies insulin sensitivity, sperm DNA fragmentation, erectile dysfunction OSAS asshened semen characteristics chronic epididymitis and epigenetic changes. The above discussion on endocrinopathies shows that excessive white adipose tissues derail the HPG axis, triggering hormonal imbalances which lead to infertility. This paper explains the interaction between insulin resistance and testosterone levels in type 2 diabetes affected men. The paper also focuses on sperm DNA fragmentation, showing the association between obesity and increased levels of sperm DNA damage, mitochondrial dysfunction and abnormality in morphology. Erectile dysfunction is focused on obesity-induced oxidative stress, inflammation and hormonal abnormalities that impair male reproductive function. Additionally, the role of sleep apnea in testosterone secretion and possible association between its severity to lower level of this hormone are presented. There is a further discussion of altered sperm traits, chronic epididymitis and epigenetic changes with regard to the obesity which gives us a broad perspective on male fertility. The paper then concludes its discussion regarding weight loss interventions restoring fertility, focusing on diet and exercise as means for reducing certain parameters associated with modifiable inflammatory markers linked to infertility. In summary, the general assessment highlights that obesity management is crucial in male infertility.